2004
DOI: 10.2151/jmsj.2004.441
|View full text |Cite
|
Sign up to set email alerts
|

Data Assimilation of GPS Precipitable Water Vapor into the JMA Mesoscale Numerical Weather Prediction Model and its Impact on Rainfall Forecasts

Abstract: Precipitable water vapor (PWV), which was obtained from the nation wide GPS (Global Positioning System) network over Japan, operated by the Geographical Survey Institute (GSI), was assimilated into the meso data assimilation (DA) system of the Japan Meteorological Agency (JMA). Two different methods were examined; one is an optimum interpolation (OI) method, and the other is a 4-dimensional variational (4D-Var) method. Using the analysis data derived from both systems, a number of forecast experiments for rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 6 publications
0
41
0
Order By: Relevance
“…Authors also noted that the forecasts work better if the ground based automatic weather stations were used in the same assimilation run. Another example of an early stage case-based research is the assimilation of GPS PW by Nakamura et al, (2004) with 4DVAR scheme into mesoscale JMA model for summer intensive rain cases. The assimilation of GPS data improved the precipitation location, but the statistics did not show large 20 improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Authors also noted that the forecasts work better if the ground based automatic weather stations were used in the same assimilation run. Another example of an early stage case-based research is the assimilation of GPS PW by Nakamura et al, (2004) with 4DVAR scheme into mesoscale JMA model for summer intensive rain cases. The assimilation of GPS data improved the precipitation location, but the statistics did not show large 20 improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Although their primary purpose is to study crustal deformation, they have a large potential as meteorological sensors. Several studies have shown that the water vapor information retrieved from GEONET has positive impacts on numerical weather prediction (NWP) (e.g., Nakamura et al 2004;Koizumi and Sato 2004;Seko et al 2004). Such previous studies conducted in Japan mainly used post processed GPS PWV data that was retrieved from a GPS analysis using a precise final ephemeris (orbits and clocks).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows that assimilation of precipitation amount data improves precipitation forecasts throughout the whole forecast period of 18 hours for both of weak and moderate pre- cipitations. Impacts of precipitable water data from GPS ground receivers or satellite microwave imagers and radial wind data from Doppler radar were also investigated with the mesoscale 4D-Var system by Nakamura et al (2004), Koizumi and Sato (2004), and Seko et al (2004).…”
Section: Mesoscale Applications Of 4d-varmentioning
confidence: 99%